First Report of Pilidiella granati on Pomegranate with Symptoms of Crown Rot in the Prefecture of Xanthi, Greece - Thomidis, T (Plant disease, 2011)
In spring 2010, plants of pomegranate (Punica granatum L.) cv. Wonderful with symptoms of crown rot were observed in the Prefecture of Xanthi, Thrace, Greece. Close examination of these plants revealed distinct symptoms of crown rots. Isolations from the lower margins of the necrotic area were made by plating tissues of approximately 3 mm on acidified (2.5 ml of 85% lactic acid per liter of nutrient medium to create a pH = 3.5 after autoclaving) potato dextrose agar. The plates were incubated at 23°C for 5 to 7 days, and consistent colonies with light yellow, leathery mycelia and abundant, black, solitary pycnidia of various sizes were observed. Hyphae were septate and conidia were hyaline, one-celled, and ellipsoid to fusiform (average 10.1 to 20.2 × 3.2 to 4.3 μm). The pathogen was identified as Pilidiella granati Saccardo (synonym Coniella granati (Saccardo) Petrak & Sydow (3)) based on mycelium and spore morphology and ribosomal ITS1-5.8S-ITS2 sequences, which were identical to GenBank No. FN908875. Koch's postulates were completed in the laboratory by inoculating 20 1-year-old plants of pomegranate cv. Wonderful. With a 7-mm-diameter cork borer, a wound was created in the middle of each collar by removing the bark. A 6-mm-diameter agar plug bearing mycelia and spores from a 15-day-old culture of P. granati was inserted into each wound. The wound was covered with petroleum jelly and wrapped with adhesive tape to prevent desiccation. Ten trees were inoculated with sterile potato dextrose agar plugs to serve as controls. All plants were incubated at 25°C for 10 days, at which time necrosis was observed. Koch's postulates were satisfied after reisolating the fungus from inoculated plants that developed symptoms similar to those observed in the field. Control plants produced no symptoms of disease. To our knowledge, this is the first report of P. granati from pomegranate plants with symptoms of crown rots in Greece. The role of predisposing factors such as herbicides and frost damage to infection by P. granati is unknown. This pathogen has been reported to cause fruit rot of pomegranate in Spain (2) and California (1). References: (1) T. J. Michailides et al. (Abstr.) Phytopathology 100(suppl.):S83, 2010. (2) L. Palou et al. New Dis. Rep. Online publication. doi:10.5197/j.2044-0588.2010.022.021, 2010. (3) G T. Tziros and K. Tzavella-Klonari. Plant Pathol. 57:783, 2007